Vinyl-2-pyrrolidone derivatized guar gum based aqueous two-phase system - Kautharapu, Kumar; Pujari, Narahari S.; Golegaonkar, Sandeep B.; Ponrathnam, Surendra; Nene, Sanjay N.; Bhatnagar, D. (Separation and Purification Technology, 2009)
Aqueous two-phase systems (ATPs) are formed when certain combinations of two polymers or polymer and salt are added to water. Phase separation occurs at certain specific concentrations that have similar densities and low interfacial tensions. The present study involves synthesis and application of a novel derivatized guar in aqueous two-phase system. The derivation of guar gum was performed by grafting of 1-vinyl-2-pyrrolidone by a redox reaction in aqueous medium ceric ammonium nitrate (CAN) and potassium Peroxydisulfate(K2S2O8). The ratio of grafting efficiency (%GE) and ratio of grafting (%G) was 56% and 70.1% respectively. The grafted copolymers were characterized for percent yield and FTIR absorbance. A new aqueous two-phase extraction protocol was established using a mixture of derivatized guar and dextran. A phase diagram was constructed based on the phase separation exhibited by the system at 25 degrees C. The partition coefficient was determined for standard bovine serum albumin (BSA), lactate oxidase (LO) and phytase. The partitioning coefficients were 0.479, 1.981, and 2.586 respectively in the Dextran (2 mill ion)/V-GG/H2O system. The influence of an ionic salt sodium chloride (NaCl) was investigated on the partitioning of BSA. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Aqueous two phase; graft copolymers; Guar gum; Partition coefficient (K); Phase diagram; Vinyl pyrrolidone; viscosity

Dripping dynamics of newtonian liquids from a tilted nozzle - Taur, Amaraja; Doshi, Pankaj; Yeoh, Hak Koon (European Journal of Mechanics B-Fluids, 2015)
The dripping dynamics of Newtonian liquids emanating from an inclined nozzle is studied. The fluid viscosity mu flow rate Q, nozzle radius R, and inclination angle theta have been varied independently. The drop breakup times and the different modes of dripping have been identified using high speed imaging. A phase diagram showing the transition between the dripping modes for different theta is constructed in the (We, Ka) space, where We (Weber number) measures the relative importance of inertia to surface tension force and Ka (Kapitza number) measures the relative importance of viscous to surface tension forces. At low values of We and Ka, the system shows a transition from period-1 to limit cycle before chaos. The limit cycle region narrows down with increase in inclination. Further increase in the values of We and Ka gives a direct transition from period-1 to chaos. The new experiments reveal that in the period-1 region, increasing the nozzle inclination angle theta results in lowering of the drop breakup time t(b), suggesting that the surface tension forces cannot hold the drops longer despite the weakened effective gravitational pull. This counter-intuitive finding is further corroborated by pendant drop experiments and computations. More curiously, throughout the period-1 regime, the drop volume is independent of the flow rate. This resulted in a relatively simple correlation for the dimensionless drop volume V = 1.3G(-1)Ka(0.02)(cos theta)(0.37) accurate to within 10% over wide ranges of the independent variables. (C) 2014 Elsevier Masson SAS. All rights reserved.
Keywords: Asymmetric dripping; Breakup time; Drop volume; Inclined nozzle; Phase diagram